Coordination instruments in Croatian integration policy : classification, evaluation, and proposals for improvements - Giljević, Teo (Array, 2018)
The key question addressed in this paper is that of connecting the institutional setting and planned outcomes of the integration policy with the instruments and types of coordination in the government system. Integration policy may be defined as a “wicked problem”, as it is a cross-sectoral issue that concerns the responsibilities of various actors. Integration is not a policy that can develop serendipitously; it needs to be designed and proper instruments of coordination should be developed. It requires coordination across different sectors and tiers of government, with both formal and informal coordination structures and instruments that can be used to facilitate coordinated implementation of policy goals and measures. Croatia has only rather recently started to develop its integration policy. Due to a relatively small number of migrants, the integration policy is primarily targeted at the refugee population. In practice, integration is an inter-departmental task dealt with by different organisations (ministries, agencies) at different governmental levels (national, local) and includes their cooperation with different non-state actors. This is very challenging in the highly fragmented and pluralistic Croatian public administration system, which lacks integrative government capacity, strategic planning, and prioritisation of developed consultative mechanisms. The paper analyses the recently promoted Croatian integration policy in the light of coordination models and instruments. It provides an overview of the types and instruments of coordination in the government system and presents the development of the Croatian migration and integration policy, its institutional setting, and the implementation of integration in practice. Finally, it provides a classification and evaluation of the coordination instruments in the integration policy.